2021
DOI: 10.3390/diagnostics12010078
|View full text |Cite
|
Sign up to set email alerts
|

Proton Density Fat Fraction Spine MRI for Differentiation of Erosive Vertebral Endplate Degeneration and Infectious Spondylitis

Abstract: Vertebral Modic type 1 (MT1) degeneration may mimic infectious disease on conventional spine magnetic resonance imaging (MRI), potentially leading to additional costly and invasive investigations. This study evaluated the diagnostic performance of the proton density fat fraction (PDFF) for distinguishing MT1 degenerative endplate changes from infectious spondylitis. A total of 31 and 22 patients with equivocal diagnosis of MT1 degeneration and infectious spondylitis, respectively, were retrospectively enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In contrast, Baum and colleagues reported normal lumbar vertebral body PDFF in young individuals (mean age 26 years) to be 35% ( 69 ). Underlining the high variability of PDFF values in different spinal pathologies, it has been recently shown that PDFF was significantly lower in infectious spondylitis compared to erosive endplate changes (4% versus 35%) ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Baum and colleagues reported normal lumbar vertebral body PDFF in young individuals (mean age 26 years) to be 35% ( 69 ). Underlining the high variability of PDFF values in different spinal pathologies, it has been recently shown that PDFF was significantly lower in infectious spondylitis compared to erosive endplate changes (4% versus 35%) ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the musculoskeletal system, the CSE-MRI-based PDFF has been primarily used for fat quantification of the bone marrow (BM) in vertebral bodies in osteoporosis or for vertebral body endplate lesions [ 1 , 12 ]. For the latter, the discrimination between Modic-type endplate lesions as a degenerative entity and infectious diseases including spondylodiscitis is a common issue for clinical imaging, which has been addressed in the work by Schmeel et al [ 13 ]. Specifically, the authors used the PDFF derived from CSE-MRI (3D six-echo modified Dixon sequence at 1.5 or 3 Tesla) for distinguishing Modic type 1 endplate lesions from infectious spondylitis, with histopathology or clinical and imaging follow-up examinations as the diagnostic reference standards [ 13 ].…”
mentioning
confidence: 99%
“…For the latter, the discrimination between Modic-type endplate lesions as a degenerative entity and infectious diseases including spondylodiscitis is a common issue for clinical imaging, which has been addressed in the work by Schmeel et al [ 13 ]. Specifically, the authors used the PDFF derived from CSE-MRI (3D six-echo modified Dixon sequence at 1.5 or 3 Tesla) for distinguishing Modic type 1 endplate lesions from infectious spondylitis, with histopathology or clinical and imaging follow-up examinations as the diagnostic reference standards [ 13 ]. The intra-vertebral PDFF and a PDFF ratio (i.e., vertebral endplate PDFF divided by normal vertebrae PDFF) were calculated within edematous BM lesions, and measurements were then compared between patients with Modic type 1 endplate lesions and patients with infectious spondylitis [ 13 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations